Population Control Policy Implementation in the Framework of National Health Insurance - Wahyudi, Fikri Mourly; Siswanto, Hadi; Hartono, Budi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The presence of National Health Insurance at the same time with the implementation of regional autonomy affects the implementation of many other policies, including population control. Different understanding and commitment of implementors resulted in mixed results, with unsuccessful trends of implementing population control policy in the frame of National Health Insurance. Cimahi as the most populous city in West Java needs to implement the policies effectively to prevent negative impact of overpopulation. An analysis needs to be conducted to assess the implementation of the policies in Cimahi. The purpose of this study was to analyze the implementation of population control policy within the framework of National Health Insurance. This research was conducted in Cimahi and used qualitative design with case study approach. Data collected through in-depth interview and questionnaires to the implementors of the policies. Data analyzed with the concept of Edwards III and Analysis Hierarchy Process. The results showed that the policies implemented facing difficulties, with National Health Insurance not necessarily encouraging population control through the use of contraceptive. It is suggested that Cimahi City Government improve policies implementation by integrating mutually supportive policies, communicating and disseminating, increasing resources, and increasing cooperation between institutions.